ChemInform Abstract: Catalytic Olefin Hydroamidation Enabled by Proton‐Coupled Electron Transfer. Issue 16 (March 2016) - Miller, David C.; Choi, Gilbert J.; Orbe, Hudson S.; Knowles, Robert R.
Abstract: A broad spectrum of unactivated olefins bearing a terminal amide function is subjected to the optimized conditions A) which include a catalyst system of 3 components.